Transcranial Focused Ultrasound Neuromodulation: A Review of the Excitatory and Inhibitory Effects on Brain Activity in Human and Animals - Zhang, Tingting; Pan, Na; Wang, Yuping; Liu, Chunyan; Hu, Shimin (Frontiers in Human Neuroscience, 2021)
Improved methods for noninvasively modulating human brain function are needed. The effects of focused ultrasound on neuronal activity have been investigated since the 1920s. FUS has been shown to modulate the activity of peripheral nerves, spinal reflexes, the cortex, and even deep brain nuclei, such as the thalamus. Unlike high-intensity ultrasound, low-intensity transcranial focused ultrasound (tFUS) can exert nondestructive mechanical pressure effects on cellular membranes and ion channels without producing cavitation and thermal injury. Therefore, it has obvious advantages in terms of security. This technology is considered to have broad application prospects in brain diseases such as neurodegenerative disorders and neuropsychiatric disorders. This review synthesizes animal and human research outcomes and offers an integrated description of the excitatory and inhibitory effects of tFUS in varying experimental and disease conditions.